The Effect of Drill Training on The Results of Smash Punches in Badminton Games on Extracurricular Male Students - Fajri, Sholawatul; Lanos, Muhsana EL Cintami; Lian, Bukman; Ardiansyah, Ari; Aljawani, Luthfi Ma’ruf (Universitas PGRI Palembang, 2023)
Sports in Indonesia continue to experience rapid development over time the development of the sport, marked by the number of Indonesian citizens who carry out sports activities in everyday life. Indonesians who carry out these sports activities have different goals. As for their purpose in doing sports activities to improve physical freshness, equal health, and to achieve achievements in certain sports fields, therefore by doing sports activities, the Indonesian people have begun to know and begin to feel the benefits of the sport.